Escherichia coli PriA protein is essential for inducible and constitutive stable DNA replication. - Masai, H (1994)
Under certain conditions, Escherichia coli cells exhibit either of two altered modes of chromosomal DNA replication. These are inducible stable DNA replication (iSDR), seen in SOS-induced cells, and constitutive stable DNA replication (cSDR), seen in rnhA mutants. Both iSDR and cSDR can continue to occur in the absence of protein synthesis. They are dependent on RecA protein, but do not require DnaA protein or the oriC site. Here we report the requirement for PriA, a protein essential for assembly of the phi X174-type primosome, for both iSDR and cSDR. In priA1(Null)::kan mutant cells, iSDR is not observed after induction by thymine starvation. Replication from one of the origins (oriM1) specific to iSDR is greatly reduced by the priA1::kan mutation. cSDR in rnhA224 mutant cells deficient in RNase HI is also completely abolished by the same priA mutation. In both cases, SDR is restored by introduction of a plasmid carrying a wild-type priA gene. Furthermore, the viability of an rnhA::cat dnaA46 strain is lost at 42 degrees C upon inactivation of the priA gene, indicating the lethal effect of priA inactivation on those cells whose viability depends on cSDR. These results demonstrate that a function of PriA protein is essential for iSDR and cSDR and suggest the involvement of the PriA-dependent phi X174-type primosome in these DnaA/oriC-independent pathways of chromosome replication. Whereas ColE1-type plasmids, known to be independent of DnaA, absolutely require PriA function for replication, DnaA-dependent plasmid replicons such as pSC101, F, R6K, Rts1 and RK2 are able to transform and to be maintained in the priA1::kan strain.(ABSTRACT TRUNCATED AT 250 WORDS)